(3JYdjb Ydi QSGdI GdcfjIs - (3eMeO GdNVQGhjs
(3ChdgG (B:s
(3GdMeO ddg NGdb CfhGY GdWHGFY hCbSGe GdCeRLI hHYO abO hbaJ Ydi gPg GdQSGdI GdefjaI hGdYLGdI GddWjaI GdcjfI cjfI ahjOJgG QSGdI MSf GdhVY s
(3BNQgG (B:s
(3eG bGdJ GdCdSf aj eOMgG QSGdI eG dgG ef fUjQ s
(3Vef eLehY , JQJjHgG (B: 9s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3eQcR GdHMK GdYdej (B- (3Ge GdbQj s
Keywords: (3eJaQbGJs